Pemenuhan Pangan Lokal Sebagai Kebutuhan Gizi Bayi Dan Balita Umur 6 -24 Bulan Di Kabupaten Banyumas - Fauziah Hanum Nur Adriyani; Arlyana Hikmanti; Rosi Kurnia Sugiharti (Jurnal Pengabdian Masyarakat - PIMAS, 2022)
One of the risk factors for stunting is lack of nutritional intake in the long term. Toddlers with poor nutritional status have a low immune system which can make them susceptible to infectious diseases. The macro nutrition improvement program is directed at reducing macro nutrition problems, which primarily address the problem of protein energy deficiency. The processing and development of local food ingredients as a source of need to overcome the stunting problem is still not widely carried out by mothers in the Banyumas Regency area.Integrated service post cadres (posyandu) and Family Welfare Development cadres (PKK) are major milestones in public health, especially infants and toddlers through their activities in mobilizing their citizens to utilize local food. So that in this activity the researchers held training for cadres, PKK mothers and mothers of babies and toddlers 6 - 24 months in all areas of Banyumas Regency in local food processing as an effort to handle and prevent nutritional problems in Banyumas Regency.Based on observations that have been made, out of all partners, around 80% of partners are skilled, and independent in implementing the processing of complementary foods made from local breast milk.